2009
DOI: 10.1099/ijs.0.009415-0
|View full text |Cite
|
Sign up to set email alerts
|

Algoriphagus olei sp. nov., isolated from oil-contaminated soil

Abstract: A motile, Gram-negative, pinkish red-pigmented bacterium (strain CC-Hsuan-617 T ) was isolated from an oil-contaminated soil near an oil refinery located in Kaohsiung County, Taiwan. 16S rRNA gene sequence analysis showed that strain CC-Hsuan-617T clustered with Algoriphagus mannitolivorans (97.5 % sequence similarity), Algoriphagus aquatilis (98.0 %) and Algoriphagus boritolerans (97.5 %), followed by Algoriphagus ornithinivorans (97.1 %) and Algoriphagus alkaliphilus (97.1 %). The fatty acid profile of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…S3). The DNA G+C content of strain W29 T was 46.2 mol%, in agreement with values reported for other members of genus Algoriphagus (Young et al, 2009). Based on phylogenetic distinctness (based on 16S rRNA gene sequences) and DNA-DNA relatedness, along with clear differences in physiochemical and chemotaxonomic characteristics, strain W29 T represents a novel species of the genus Algoriphagus, for which the name Agoriphagus roseus sp.…”
Section: Algoriphagus Boseongensis Bs-r1 T (Kf768344) 'Algoriphagus Ssupporting
confidence: 85%
“…S3). The DNA G+C content of strain W29 T was 46.2 mol%, in agreement with values reported for other members of genus Algoriphagus (Young et al, 2009). Based on phylogenetic distinctness (based on 16S rRNA gene sequences) and DNA-DNA relatedness, along with clear differences in physiochemical and chemotaxonomic characteristics, strain W29 T represents a novel species of the genus Algoriphagus, for which the name Agoriphagus roseus sp.…”
Section: Algoriphagus Boseongensis Bs-r1 T (Kf768344) 'Algoriphagus Ssupporting
confidence: 85%
“…1A), and their higher contribution to the NAG‐active community was paralleled by their rising abundances. The ability to grow on NAG seems to be widespread within this group, because 13 of 16 tested Algoriphagus type‐strains were capable of NAG utilization (Young et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, we found that it is present in 100% (18/18) of Photorhabdus genomes in our dataset with 2-5 eCIS operon copies per genome (Fisher exact test, odds ra o = infinity, q value = 2.97e -28 ), 89% of sequenced Chi nophaga (odds ra o = 276, q value = 1.69e -35 ), 86% of sequenced Dickeya (odds ra o = 211, q value = 3.78e -52 ), and 69% of sequenced Algoriphagus (odds ra o = 73, q value = 1.99e -24 ). These genera are known as environmental microbes; Photorhabdus is a commensal of entomopathogenic nematodes 18 , Chi nophaga is a soil microbe and a fungal endosymbiont 19 , Dickeya is a plant and pea aphid pathogen 20,21 , and Algoriphagus is an aqua c or terrestrial microbe [22][23][24][25][26] . In contrast, eCIS is strongly depleted from the most cultured and sequenced genera of Gram-posi ve and nega ve human pathogens, including Staphylococcus , Escherichia , Salmonella , Streptococcus , Acinetobacter , and Klebsiella .…”
Section: Ecis Displays a Highly Biased Taxonomic Distribu Onmentioning
confidence: 99%